PENGARUH RASIO SOLVABILITAS DAN RASIO PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR HEALTHCARE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2024 - M. Dedy Eko Trisyono Safari; Laila Dewi Anggraeni; Hevi Susanti (JAMER : Jurnal Akuntansi Merdeka, 2026)
This study aims to examine the extent to which solvency and profitability influence firm value, both individually and simultaneously. The independent variables in this study are solvency, measured by the Debt to Equity Ratio (DER), and profitability, measured by Return on Assets (ROA). The dependent variable is firm value, which is proxied by Price to Book Value (PBV). The population of this study consists of 34 healthcare sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Using a purposive sampling technique, 14 healthcare companies were selected as research samples. The findings indicate that solvency does not have a significant partial effect on firm value, as reflected by a significance value of 0,723>0,05. In contrast, profitability has a significant positive effect on firm value, with a significance value of 0,000<0,05. Simultaneously, solvency and profitability have a significant effect on firm value, indicated by a significance value of 0,000<0,05.